Power generation from cheese whey using enzymatic fuel cell. (1st May 2020) - Choi, Han Suk; Yang, Xiaoguang; Kim, Dong Sup; Yang, Ji Hyun; Han, Sung Ok; Park, Chulhwan; Kim, Seung Wook
Abstract: As an organic waste of dairy manufacture, cheese whey was considered to be an environmental pollutant because of its high lactose content. Reutilization of lactose from cheese whey for power generation could be a novel solution for dairy industry. In this study, lactose was demonstrated as a fuel for power generation by enzymatic fuel cell (EFC) using cellobiose dehydrogenase (CDH). The enzyme was immobilized and characterized on the mediator modified electrode. To enhance the performance, various factors of this EFC system such as enzyme concentration, reaction pH, and initial concentration of lactose were investigated. The maximum current and power density were obtained at CDH concentration of 47.07 mg/ml and 100 mM lactose at pH 4.5 for EFC. The open circuit voltage and maximum power density of the EFC at optimum conditions were 0.52 V and 2, 973 μW/cm 2, respectively. Additionally, the cheese whey from dairy industry was directly demonstrated in this EFC and power density of 1, 839 μW/cm 2 was obtained. These results indicated positive prospects of cheese whey for the application of power generation, which demonstrated the feasibility of the organic waste from diary manufacture to produce a clean product.